Smart Dental Card Game Model as An Effort to Improve Behavior of Health Care For Elementary School Students - lely Surya Ningsih; Bedjo Santoso; Tri Wiyatini; Diyah Fatmasari; Waljuni A Rahman (Alta Dharma Publisher, 2020)
Correct teeth brushing behavior in elementary school children in Indonesia is 2.8%, and in Central Java, 1.7%. The influencing factor is the lack of information sources, so it is essential to carry out dental and oral health education,